Implementasi Program Latihan Fisik Berbasis Evaluasi Kondisi Fisik pada Atlet Putra Wong Palembang Sport Climbing Club (WPSCC) - Jenius Sanjaya; Noviria Sukmawati; Bayu Hardiono (Jambura Arena Pengabdian, 2026)
This community service program was conducted to address the challenges faced by Wong Palembang Sport Climbing Club (WPSCC), where physical training had not yet been implemented through a structured, measurable, and evaluation-based program, resulting in limited monitoring of athletes' physical development. The program aimed to improve the physical fitness of male sport climbing athletes aged 5–15 years through mentoring in the implementation of a structured physical training program designed based on baseline physical assessments and age-specific athlete characteristics. The activity was carried out from April to June 2026 and involved 12 male athletes. The implementation consisted of needs assessment, baseline physical testing (pre-test), development of a structured physical training program, participatory training assistance, and final evaluation through post-test measurements. The training program included jogging, dead hang/pull-up, sit-ups, squats, wall squats, ABC drills, and climbing technique practice. The results demonstrated improvements in all measured physical fitness components. Athletes aged 5–9 years showed average improvements of 27.59% in sit-up performance and 20.00% in squat performance, while athletes aged 10–15 years improved by 6.20% in pull-ups, 13.75% in sit-ups, and 10.57% in squats. In addition, the program enhanced athletes' motivation, discipline, and participation throughout the training sessions. These findings indicate that an evaluation-based physical training mentoring program is effective in supporting sport climbing clubs to implement a more systematic, measurable, and sustainable athlete development program, thereby strengthening the physical foundation of young athletes and supporting long-term performance development.